(untitled) (Bangladesh Journal of Pharmacology, 2016)
An efficient solvent-free synthesis of a 10-member library of octanoyl linked substituted aryl thioureas was accomplished successfully. The octanoyl isothiocyanate was freshly prepared in excellent yield and purity by the reaction of potassium thiocyanate with octanoyl chloride followed by removal of potassium chloride by filtration. The reaction of the latter with a series of ten different substituted anilines by stirring at 60-65°C lead to the formation of the title compounds. The in vitro antifungal activity of newly synthesized compounds was evaluated against Aspergillus niger, A. flavus and Fusarium solani strains of pathogenic fungi. Antibacterial assay was carried out against Gram positive (Staphylococcus aureus, Micrococcus luteus) and Gram negative bacterial strains (Escherichia coli, Enterobacter aerogens). Furthermore, anti-oxidant potential and enzyme inhibition studies against ?-amylase and butyryl cholinestrase were performed. The results obtained indicated moderate to excellent activities of most of the compounds whilst some derivatives showed potency higher than the standard used. Video Clips of Methodology: Antibacterial assay: 2 min 16 sec Full Screen Alternative Enzyme inhibition: 1 min 27 sec Full Screen Alternative